1989
DOI: 10.1148/radiology.171.1.2928520
|View full text |Cite
|
Sign up to set email alerts
|

Cranial bone marrow in children: assessment of normal development with MR imaging.

Abstract: Magnetic resonance images of cranial bone marrow in 238 patients (246 examinations) less than 25 years old were reviewed to establish normal age-related standards. Bone marrow in the clivus and calvaria had uniformly low signal intensity (grade 1) on T1-weighted images in most infants less than 1 year old. The number of patients with grade 1 marrow decreased rapidly in early childhood, while the number of patients with marrow of low and high signal intensity (grade 2) and uniformly high signal intensity (grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 0 publications
2
37
1
2
Order By: Relevance
“…In the qualitative assessment of clivus bone marrow related to age, our results were different from the findings of Okada et al (1989) and Kimura et al (1990). Our percentages of graded clivus bone marrow per decade were closer to the results of Oyar et al (1996).…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…In the qualitative assessment of clivus bone marrow related to age, our results were different from the findings of Okada et al (1989) and Kimura et al (1990). Our percentages of graded clivus bone marrow per decade were closer to the results of Oyar et al (1996).…”
Section: Discussioncontrasting
confidence: 85%
“…2). Clivus bone marrow showing uniform low signal intensity was graded I, bone marrow consisting of mixed low and high signal intensity portions throughout the clivus was graded II, and clivus bone marrow showing high signal intensity was graded III; this grading system was used previously by Okada et al (1989), Kimura et al (1990), and Oyar et al (1996).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique was proven useful in the assessment of bone marrow pathologies and metastatic marrow diseases (18,19). Some studies utilized conventional MRI to evaluate signal characteristics of cranial marrow (14,18,(20)(21)(22). Some authors found that MRI findings could be used as predictors for distinguishing leukemic patients from normal controls, providing more accurate diagnosis (7).…”
Section: Discussionmentioning
confidence: 99%